'Doing' memory: performativity and cultural memory in Janet Cardiff and George Bures Miller's Alter Bahnhof Video Walk. Issue 2 (2nd April 2020) - Bertens, Laura M.F.
ABSTRACT: Remembrance of the Holocaust is fraught with difficulty and as survivors pass away, our understanding moves from communicative to cultural memory. In exploring ways to successfully engage audiences, artists take up the notion of the monument and extend its boundaries. An example is Cardiff and Bures Miller's Alter Bahnhof video walk (2012), which invites its participants to critically consider the notion of monumentalisation, the nature of photographic media and the interplay between performativity and performance. This essay discusses the relationship between photographic media, memory and art, illustrating this through an analysis of the video walk.